The Influence Of Product Quality, Brand Image And E-Word Of Mouth On The Decision To Purchase Online Clothing Products Notbrand.Co In Dki Jakarta - Rani Yulia; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of the t-test on the variables of product quality, brand image, and e-word of mouth on purchasing decisions for online clothing products notbrand.co in DKI Jakarta. The sample in this study was 96 respondents who made purchasing decisions on social media based on the Anderson formula. This study uses primary data with data collection methods through questionnaires distributed to 96 respondents. The data analysis technique was using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) version 26.0 program. From the results of the t test, it shows that the product quality variable (X1) has an influence of 2.764% or 27.64%, the brand image variable (X2) has an influence of 4.878 or 48.78%, and the e-word of mouth variable (X3 ) has an influence of 2.351% or 23.51% on purchasing decisions. Thus, it can be concluded that product quality, brand image and e-word of mouth variables influence purchasing decisions.